Effect of the previous administration of medical ozone on acute mortality induced by the digoxine in mice (Ozone Therapy Global Journal, 2014)
Several reports of basic and clinical studies have suggested a beneficial effect of the administration of ozone in the heart contraction, starting from experiments in isolated heart, and in clinical investigations. However, studies don’t exist on the interaction of the medical ozone with other pharmacological agents used chronically in the treatment of heart failure. The objective of the present work was to study the interaction of the medical ozone with digoxin, through the cardiotoxic action of the latter. In the experiments male mice C-57 from 20 g to 24 g of corporal weight were used. Four groups divided in 6 subgrups of 6 animals each, were used. Two of the groups received oxygen (control) or ozone-oxygen (1.2 mg/kg), correspondingly, in volumes of 0.5 mL, 30 min before intraperitoneal administration digoxine was performed, in doses of 2, 2.5, 3.0, 3.5, 4.0 and 4.5 mg / kg respectively. The other two groups received oxygen or ozone-oxygen during 6 serial days and digoxine 24 h later, using the referred route and dose. For the calculation of DL10, DL50 and DL90, as well as for the analysis of the parallelism and displacement of the dose-response curves, the method of LIchtfield and Wilcoxon (computerized) was used. The results showed increase in digoxina toxicity in the group treated with ozone, when compare to oxygen treated group.